Strengthening Critical Thinking Skills of Prospective Teachers Through Applications Of Vedic Mathematics - S, Dr. Smitha (International Journal of Scientific Research and Management (IJSRM), 2017)
Good teachers form the foundation of good schools, and improving teachers‟ skills and knowledge is one ofthe most important investments of time and money that local, state, and national leaders make ineducation. Our changing goals for learning, coupled with shifts in curriculum emphasis and a deeperunderstanding of teacher learning and student thinking, have led to new findings about the impact of teacherprofessional development and how best to sharpen teachers‟ skills and knowledge. Teachers are expected toteach as per the curriculum, take care of all round development of children, develop abilities such aslearning how to learn, problem solving, creative thinking, which are crucial for living effectively in theworld rapidly changing with the developments in science and technology. A person who does not possessthe skills and competencies required for the tasks expected of the teacher cannot be called a teacher. Whatmatters most is what teachers learn. Professional development should improve teachers‟ knowledge of thesubject matter that they are teaching, and it should enhance their understanding of student thinking in thatsubject matter.